2013
DOI: 10.1007/s11517-013-1060-7
|View full text |Cite
|
Sign up to set email alerts
|

Assisting vascular access surgery planning for hemodialysis by using MR, image segmentation techniques, and computer simulations

Abstract: The surgical creation of a vascular access, used for hemodialysis treatment of renal patients, has considerable complication rates (30-50 %). Image-based computational modeling might assist the surgeon in planning by enhanced analysis of preoperative hemodynamics, and in the future might serve as platform for outcome prediction. The objective of this study is to investigate preoperative personalization of the computer model using magnetic resonance (MR). MR-angiography and MR-flow data were obtained for eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Currently, 2 predictive models that use ultrasonographic findings and non-gadolinium contrast-enhanced magnetic resonance angiography provide anticipated vascular access blood flow rates before vascular access surgery is attempted. 34,35 Such predictive models offer the way forward in conjunction with excellent clinical judgment that considers the individual clinical and functional characteristics, life circumstances, and preferences of patients.…”
Section: Antimicrobial/antibiotic Hd Catheter Locksmentioning
confidence: 99%
“…Currently, 2 predictive models that use ultrasonographic findings and non-gadolinium contrast-enhanced magnetic resonance angiography provide anticipated vascular access blood flow rates before vascular access surgery is attempted. 34,35 Such predictive models offer the way forward in conjunction with excellent clinical judgment that considers the individual clinical and functional characteristics, life circumstances, and preferences of patients.…”
Section: Antimicrobial/antibiotic Hd Catheter Locksmentioning
confidence: 99%
“…Following-up on the work of Bode, a more recent study uses non contrast enhanced magnetic resonance angiography (NCE-MRA) to provide arterial characteristics and semi quantitative venous characteristics [8]. This study from Netherlands aimed to assess the effect of geometric input on prediction of blood flow in vascular access using a generic circulation model with individualization limited to arm geometry (arterial diameters by NCE-MRA and venous parameters by US) and arterial flow using duplex ultrasound.…”
Section: Predictive Medicine In Vascular Access Carementioning
confidence: 99%
“…It has been shown that the patient-based preoperative geometric and hemodynamic characteristics of the circulatory system with the use of computational fluid dynamics (CFD) can assist the physician during the treatment planning. 15,16 In this paper, we initiate a study to ascertain the homeostatic shear level of the brachial artery (BA) and cephalic vein (CV). These vessels are commonly utilised and manipulated to some degree to form a fistula in the upper arm.…”
mentioning
confidence: 99%